Dental Status and Periodontal Health of Patients with Phenylketonuria in Latvia - Iveta Abola; Darta Elizabete Emulina; Ingus Skadins; Anda Brinkmane; Linda Gailite; Madara Auzenbaha (University of Zagreb. School of Dental Medicine, 2022)
Objectives: Phenylketonuria (PKU) is an autosomal recessive inherited disorder of phenylalanine metabolism resulting from a deficiency of phenylalanine hydroxylase. The aim of this study was to evaluate the dental status and periodontal health of PKU patients in Latvia. Material and Methods: Fortyfive PKU patients and age/sex-matched controls were recruited for this cross-sectional study. Their anamnestic data, periodontal health and dental status were assessed by one experienced dentist. Results: Dental and periodontal clinical evaluation revealed that the median number of filled teeth was significantly smaller among PKU patients compared to the control group (p=0.021). PKU patients had a significantly larger median number of carious teeth than their healthy counterparts (p<0.001). Significant differences between the PKU and control groups were observed for several oral hygiene indices (p<0.001): Silness-Löe plaque index, OR=29.3 (95% CI: 3.7-232.4); CPITN index, OR=35.2 (95% CI: 4.5-278.3); Greene-Vermillion index, OR=10.2 (95% CI: 2.8-38.0); calculus removal necessity, OR=12.3 (95% CI: 3.3-45.4). Conclusion: Dental status and periodontal health of PKU patients was found to be significantly inferior compared to healthy controls. This is likely due to the regular consumption of PKU formula and the difficulties which mentally and/or physically disabled PKU patients experience with their oral hygiene. To prevent tooth decay and periodontal disease, PKU patients should visit a professional oral hygienist every three to six months. Furthermore, they should adopt the habit of rinsing their mouth with water immediately after consuming PKU formula to counteract the acidity in their oral cavity.